Measuring Children's Stress via Saliva in Surgical and Endoscopic Procedures and Its Measurement Intention in the Community: Reality-Future Prospects - Maria Grigoropoulou; Achilleas Attilakos; Anestis Charalampopoulos; Smaragdi Fessatou; Efstratios Vamvakas; Anastasia Dimopoulou; Nikolaos Zavras (MDPI AG, 2023)
(1) Background: Children who undergo surgical or endoscopic procedures display high levels of stress, and various means are applied to reduce their anxiety. Salivary cortisol (S Cortisol) and salivary alpha-amylase (SAA) are often used as a valid biomarker of stress. The primary purpose of the study was the investigation of stress levels through S Cortisol and S amylase after intervention in surgical or endoscopic procedures (gastroscopy-colonoscopy). The secondary outcomes were the investigation of the intention to adopt new methods of saliva sampling. We collected saliva samples from children subjected to invasive medical procedures, with the aim of applying the Theory of Planned Behavior (TPB) as an intervention means to provide information and education to both parents and children undergoing stressful situations, and assess its efficacy in reducing stress levels. We also aimed at acquiring a better understanding of the acceptability of noninvasive biomarker collection in community settings. (2) Methods: The sample of this prospective study comprised 81 children who underwent surgical or endoscopic procedures at the Attikon General University Hospital, Athens, Greece and 90 parents. The sample was divided into two groups. The first, 'Group Unexplained', was not provided any information or education about the procedures, while the second, 'Group Explained', was informed and educated based on TPB. Thereafter, 8-10 weeks after intervention, the Theory of Planned Behavior questions were re-completed by the 'Group Explained'. (3) Results: Significant differences were detected in cortisol and amylase values between the two groups postoperatively after applying the TPB intervention. Saliva cortisol was reduced by 8.09 ng/mL in the 'Group Explained' while in the 'Group Unexplained' it was reduced by 4.45 ng/mL (p < 0.001). Salivary amylase values decreased by 9.69 ng/mL in the 'Group Explained' after the intervention phase of the study, while in the 'Group Unexplained' they increased by 35.04 ng/mL (p < 0.001). The regression explains 40.3% (baseline) and 28.5% (follow-up) of parental intention. The predictive factor of parental intention (baseline) is attitude (p < 0.001) and follow-up is behavioral control (p < 0.028) and attitude (p < 0.001). (4) Conclusions: Providing proper education and information for parents has a positive effect on reducing children's stress levels. Changing parental attitudes towards saliva collection plays the most important role, since a positive attitude can influence intention and ultimately participation in these procedures.